Exploring The Tasting System and Clinical Significance of Taste Disorders: A Narrative Review: Clinical Significance of Taste Disorder - Giovani Indah Giantoro Putri; Soehartono; Yunisa Astiarani (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2023)
Introduction: This review took an in-depth look at the intricate anatomy of taste buds, unveiling their complex structure and function, delved into the fascinating mechanisms that underlie taste transmission, shedding light on how sensory information is relayed from the taste buds to the brain, enabling us to perceive and differentiate various flavors.Result and Discussions: This narrative review indicates that diverse factors can induce changes in taste buds, ranging from genetic predispositions to external influences such as medications and lifestyle habits. By comprehensively understanding these factors, healthcare professionals and researchers can better identify the root causes of taste problems and devise effective management strategies. Recognizing the clinical significance of taste-related issues is crucial in providing appropriate care and support to individuals experiencing taste disorders.Conclusions: Despite significant advancements in understanding the gustatory function and molecular mechanisms of taste receptor cells, there still needs to be a comprehensive clinical understanding regarding the underlying causes and mechanisms of taste disorders in humans. Keywords: Tasting System - Taste Disorder – Gustatory - Clinical Significance